White Peach Scale, Pseudaulacaspis pentagona (Targioni) - Deanna Branscome (EDIS)
This document is EENY-076, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 1999.